Preparation and potential of nanoparticles containing curcuminoids to control fungal diseases in tropical fruits - Le Dang Quang; Nguyen Tuan Anh; Tran Quang De; Nguyen Thi Thu Trang; Vu Xuan Minh; Nguyen Cuong Quoc; Vo T. Kieu Anh; Bui Van Cuong; Tran Dai Lam; Tran Thanh Men; et al. (Vietnam Journal of Science and Technology, 2023)
Colletotrichum species cause anthracnose in various tropical crops in both cultivation and postharvest periods. The current synthetic fungicides to treat anthracnose sometime show toxic effects for farmers, residues on foods, and environmental impacts. In this work, turmeric extract containing curcuminoids was used as an active ingredient and formulated into a nanoemulsion to control anthracnose in red pepper and tomato fruits. The nanoparticles containing turmeric extract (25 %) were successfully prepared by encapsulation using Tween-80 and PEG 400 as emulsifiers. Out of the three main curcuminoids in the turmeric extract, BDMC was determined as the most abundant constituent via HPLC analysis. Turmeric nanoparticles showed an average particle size of 203 nm, polydispersity index (PI) of 0.322, and zeta potential of -92.7 mV. In the in vitro antifungal bioassay, this nanoformulation significantly inhibited the mycelial growth of Colletotrichum gloeosporioides and Colletotrichum orbiculare in a dose-dependent manner. Red pepper anthracnose was also consistently suppressed by turmeric nanoparticles but the tomato anthracnose was resistant to this formulation at 10 mg/mL in vivo. The study results proved the effectiveness of turmeric nanoparticles to control red pepper anthracnose in postharvest preservation and suggested developing the innovative nanoformulation as a green fungicide.